Implementation of a method for the identification and quantification of phytosterols in peanut (Arachis hypogaea L.) by gas chromatography - Aquilano, Claudio Gabriel (2025)
Peanut (Arachis hypogaea L.), a major source of oil, is the second most widely cultivated legume crop worldwide after soybean. Argentina is the largest producer of confectionery peanuts in Latin America and the seventh in the world. This legume has bioactive compounds of nutritional value, phytosterols among the most important ones. Phytosterols protect against cancer and lower cholesterol rates. The objective of this work was to adjust and refine a method to identify and quantify phytosterol content in peanut seeds by gas chromatography. The method was found to be accurate, as demonstrated through repeatability and reproducibility tests, and expressed by the coefficients of variation. No significant differences were found between the results obtained and the reference values using a confidence level of 95 % and 5 degrees of freedom. The results obtained in this work presented 44.31 mg of beta-sitosterol and 3.39 mg of stigmasterol per 100 g of roasted peanuts, in agreement with the values reported in the literature.